(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of the analysis of the current state of post-harvest treatments and new technologies that can be used to maintain the quality and reduce losses of fresh produce are presented. The analysis of modern domestic and foreign scientific and patent literature indicates that various post-harvest physical, chemical and gas treatments can be used to preserve the quality of fresh produce with high nutritional value and compliance with safety standards for fresh vegetables and fruits. These post-harvest treatments are usually combined with proper storage temperature control. Results. The main advantages of using coatings are based on such properties as cost, availability, functionality, mechanical properties, optical properties, resistance to damage by microorganisms and sensory acceptability. They are used in combination with bioactive compounds that provide fruits and vegetables with additional functions, reduce weight loss and quality preservation and extend shelf life. The principle is to reduce respiration, delay post-harvest ripening of fresh fruits and vegetables and prevent the reproduction of microorganisms. Technological advances have led to the development of cutting-edge equipment for preserving fresh produce, such as modified atmosphere, controlled atmosphere, vacuum packaging, cold plasma, freezing and chilling. However, the high cost and significant energy requirements of these advanced technologies make them inaccessible to small-scale producers in developing countries. They are also unprofitable for retailers and will certainly affect household financial portfolios. Knowing that in today’s world, environmentally friendly and energy-efficient technologies attract customers, we propose approaches and methods that are easy to implement, affordable and energy-efficient, and that benefit smallholders, retailers and consumers.